Thermal Simulation and Analysis of the Single LED Module - Dinh, Van Quyen; Nguyen, Nhu Nam; Nguyen, Ngoc Anh; Nguyen, Duc Tung; Doan, Quang Tri; Ta, Quoc Tuan; Nguyen, DucTrung Kien; Pham, Thanh Huy; Dao, Xuan Viet (Smart Systems and Devices, 2021)
Light Emitting Diodes (LED) shows an important role in replacing traditional lamps due to their longevity, high efficiency, and environment-friendly operation. However, a large portion of the electricity applied on LED converts to heat, raising up the p-n junction working temperature, and lowering the output-light quality and the LED lifetime as well. Therefore, thermal management for LED is one of the key issues in LEDs lighting application. In order to investigate the impact of each component of the LED module on the junction temperature of the LED, we have performed thermal simulations of a typical single LED module by using the finite element method. Effects of thermal conductivity and thickness of each module’s components on junction temperature were analyzed systematically. The results provided a detailed understanding of thermal behavior of a single LED module and established a crucial insight into thermal management design for high-power white LED lamp. Thermal-interface-materials (TIM) and the dielectric layer are proposed to have thermal conductivity around 1 W/mK for system optimization. In addition, based on the thermal analysis of heat sink, we have proposed and investigated a new configuration of plastic heat sink embedded with aluminum-alloy. The thickness ratio between the embedded aluminum layer and the heatsink base is suggested to be around 0.1 to 0.15 for the optimal configuration.